2014
DOI: 10.7150/ijms.9529
|View full text |Cite
|
Sign up to set email alerts
|

DHRSX, A Novel Non-Classical Secretory Protein Associated With Starvation Induced Autophagy

Abstract: Dehydrogenase/reductase (SDR family) X-linked (DHRSX) is a novel human gene without any substantial functional annotation and was initially cloned and identified in our laboratory. In this study, we present evidence that it encodes a non-classical secretory protein and promotes starvation induced autophagy. Using the Baf.A1 assay and N-terminal sequencing, we showed that DHRSX is secreted in a non-classical form. We expressed and purified a recombinant human GST-DHRSX fusion protein. Functional studies reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Next, we explored the functions of the hub genes and found that numerous genes were associated with the autophagy process including DEPDC, DHRSX, ATG2A, and C9orf72. These four genes have been reported to be involved in the regulation of autophagy ( Zhang et al, 2014 ; Bakula et al, 2017 ; Wang W. et al, 2020 ; Pang and Hu, 2021 ), and they also showed good classification efficiency in ROC analysis. In addition, DEPDC and DHRSX were highly correlated with NK cell activation.…”
Section: Discussionmentioning
confidence: 91%
“…Next, we explored the functions of the hub genes and found that numerous genes were associated with the autophagy process including DEPDC, DHRSX, ATG2A, and C9orf72. These four genes have been reported to be involved in the regulation of autophagy ( Zhang et al, 2014 ; Bakula et al, 2017 ; Wang W. et al, 2020 ; Pang and Hu, 2021 ), and they also showed good classification efficiency in ROC analysis. In addition, DEPDC and DHRSX were highly correlated with NK cell activation.…”
Section: Discussionmentioning
confidence: 91%
“…SGTA, down-regulated in CCM2-KO zebrafish, is not characterized very well but has been shown to interact with 70-kDa heat shock cognate protein and hypothesized to serve housekeeping functions (Liu et al., 1999; Paul et al., 2014). DHRSX, up-regulated only in CCM1 deficient cells, is relatively uncharacterized other than being hypothesized in having a role in positive regulation of starvation-induced autophagy (Zhang et al., 2014). Previous data showed that down-regulation of integrin β4 promotes sphingosylphosphorylcholine-induced autophagy (Ge et al., 2011), suggesting that perturbed autophagy can be observed in CCMs.…”
Section: Discussionmentioning
confidence: 99%
“…DHRSX gene is a new gene discovered in 2014 at the Xp22.33 and Yp11.2 in the human genome. It has been shown that the protein encoded by this gene is implicated in the positive regulation of starvation induced autophagy [ 54 ].…”
Section: Resultsmentioning
confidence: 99%